Analyzing the factors that influencing the success of post graduates in achieving graduate on time (GOT) using analytic hierarchy process (AHP) - Chin, Wan Yung; Ch’ng, Chee Keong; Mohd Jamil, Jastini; Mohd Shaharanee, Izwan Nizal (IP Publishing LLC, 2017)
In the globalization era, education plays an important role in educating and preparing individuals to face the demands and challenges of 21st century.Thus, this contributes to the increase of the number of individuals pursuing their studies in Doctor of Philosophy (Ph.D) program.However, the ability of Ph.D students in heading to the four years Graduate on Time (GOT) mission that is stipulated by University has become a major concern of students, institution and government.Therefore, the main objective of this study is to investigate the factors that influence the Ph.D students in Universiti Utara Malaysia (UUM) to achieve GOT.Through the reviewing of previous research, six factors which are student factor, financial factor, supervisor factor, skills factor, project factors and institution factor had been identified as the domain factors that influence the Ph.D students in achieving GOT.The level of importance for each factor will be ranked by the experts from three graduate schools using Analytic Hierarchy Process (AHP) technique. This study will bring a significant contribution to the understanding of factors that affecting the Ph.D students in UUM to achieve GOT. In Addition, this study can also succor the university in planning and assisting the Ph.D students to accomplish the GOT in future.